Lo exterior y lo interior en la modernidad /colonialidad (De La Escena Contemporánea) - León Pesántez, Catalina Soledad (2015)
The article aims to explore hiatal Modernity/coloniality from a form of rationality linked to the practices of identity and difference, from whose edges are untied complex joints that demand to be seen in their constant actuality and historicity. In the exterior and interior of modernity/ coloniality, we can find fluctuating “eventualities” that re-update “asynchronies” as historical demands that must be made explicit.